2021
DOI: 10.18632/aging.202908
|View full text |Cite
|
Sign up to set email alerts
|

Hsa-miR-107 regulates chemosensitivity and inhibits tumor growth in hepatocellular carcinoma cells

Abstract: Hepatocellular carcinoma is a common type of liver cancer. Resistance to chemotherapeutic agents is a major problem in cancer therapy. MicroRNAs have been reported in cancer development and tumor growth; however, the relationship between chemoresistance and hepatocellular carcinoma needs to be fully investigated. Here, we treated hepatocellular carcinoma cell line (HA22T) with a histone deacetylase inhibitor to establish hepatocellular carcinoma-resistant cells (HDACi-R) and investigated the molecular mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The deregulation of miR-107 expression has been implicated in various human cancers, with its role as either a tumor suppressor or an oncogene being debated [41][42][43]. This debate also extends to liver cancer, where studies have reported both carcinogenic [44] and tumor-suppressive effects of miR-107 [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…The deregulation of miR-107 expression has been implicated in various human cancers, with its role as either a tumor suppressor or an oncogene being debated [41][42][43]. This debate also extends to liver cancer, where studies have reported both carcinogenic [44] and tumor-suppressive effects of miR-107 [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…miR-107 belongs to a highly conserved miR-15/miR-107 gene family that shares a common “AGCAGC” sequence near the end of the mature miRNAs’ 5′UTR ( Finnerty et al, 2010 ). miR-107 is transcribed from the host gene PANK1 , which is broadly expressed in many tissues and has been implicated in cancers ( Turco et al, 2020 ), chemosensitivity ( Chen et al, 2021 ), ischemic stroke ( Yang et al, 2014 ), insulin resistance ( Yang et al, 2020 ), and neuronal differentiation ( Croizier et al, 2018 ). Dysregulation of miR-107 is associated with diverse pathways, including: obesity and diabetes ( Foley and O'Neill, 2012 ), Alzheimer’s disease ( Chang et al, 2017 ), cancers ( Turco et al, 2020 ; Chen et al, 2021 ), and drug treatment and environmental exposure ( Chou et al, 2017 ; Chen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…miR-107 is transcribed from the host gene PANK1 , which is broadly expressed in many tissues and has been implicated in cancers ( Turco et al, 2020 ), chemosensitivity ( Chen et al, 2021 ), ischemic stroke ( Yang et al, 2014 ), insulin resistance ( Yang et al, 2020 ), and neuronal differentiation ( Croizier et al, 2018 ). Dysregulation of miR-107 is associated with diverse pathways, including: obesity and diabetes ( Foley and O'Neill, 2012 ), Alzheimer’s disease ( Chang et al, 2017 ), cancers ( Turco et al, 2020 ; Chen et al, 2021 ), and drug treatment and environmental exposure ( Chou et al, 2017 ; Chen et al, 2020 ). In parallel, CYP substrate drug clearance and expression of the CYP enzymes also change in many of these events, such as obesity ( Brill et al, 2012 ), diabetes ( Darakjian et al, 2021 ), and cancers ( Fahy et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…These ndings show evidence that, HDACi-R cells are resistant to SAHA with increased cell viability compared to that of parental HA22T cells. miR-342-5p is a key regulator of cell survival in HDACi-R and HA22T cells microRNAs are important in tumor development and growth regulation [25]. The impact of miRNAs on HCC drug resistance was examined in HDACi-R and HA22T cell types and their differential miRNA expressions were determined using microarray analysis.…”
Section: Assessment Of Hdaci-r Cell Propertiesmentioning
confidence: 99%